HPB P47 Management of acalculous cholecystitis: Experiences from a district general hospital. (7th December 2022) - Suresan, Srutti; Shaukat, Mubasher; Ahmad, Reddin; BinSahl, Abdullah; Naeem, Hamza; Peter, Mark
Abstract: Background: Acalculous cholecystitis (AC) is a serious inflammatory condition of the gallbladder with associated high morbidity and mortality. Definitive management of AC involves cholecystectomy and/or cholecystostomy in combination with antibiotic therapy. Due to the lack of consensus regarding the optimal management of AC leading to possible variability in clinical practice, this study aims to review the management of AC in this busy district general hospital. Methods: Data were collected retrospectively on consecutive patients with diagnosis of cholecystitis from March 2018 to March 2020. The data was analysed and patients with confirmed gallstones on imaging and no clinical/radiological signs of cholecystitis were excluded. In this two-year study period, a total of 61 patients were treated for AC. Results: Twenty-eight patients were managed conservatively with antibiotics (median age of 68 and median ASA of 2). Thirty-three patients were offered definitive management; cholecystostomy (2 inpatients), laparoscopic cholecystectomy (9 inpatients and 13 elective patients), 5 remain on the waiting list for surgery and 4 declined surgery. Among patients who were offered definitive management, the median age was 62 and median ASA was 2. Seven patients developed complications of AC; 2 patients underwent acute laparoscopic cholecystectomy, 2 patients were offered elective laparoscopic cholecystectomy after having a cholecystostomy, 1 patient underwent cholecystostomy, 1 patient was offered elective laparoscopic cholecystectomy after antibiotic treatment and 1 patient was treated with antibiotics alone. 30-day readmission rate was similar between patients with conservative management (5 patients) and definitive management (4 patients). Conclusions: With similar re-admission rates, this small study suggests that definitive management options may not be superior to antimicrobial therapy alone and demonstrates that management can be tailored according to clinical needs. A larger prospective study is recommended to fully assess the efficacy and safety of laparoscopic cholecystectomy, cholecystostomy and antibiotic therapy in managing AC.